1995
DOI: 10.1007/bf02425939
|View full text |Cite
|
Sign up to set email alerts
|

Gadopentetate-dimeglumine-enhanced MR imaging of osteonecrosis and osteochondritis dissecans of the elbow: initial experience

Abstract: Magnetic resonance imaging (MRI) was performed on seven patients with aseptic osteonecrosis (n = 4) and osteochondritis dissecans (OCD; n = 3) of the elbow. Precontrast MRI was superior to plain radiographs, which did not show any abnormality in three cases of osteonecrosis. On gadopentetate-dimeglumine-enhanced T1-weighted images, which were obtained in three patients with osteonecrosis and three patients with OCD, all cases of osteonecrosis demonstrated homogeneous enhancement of the lesions. All cases of OC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Clinically, a comparison of some contrast-enhanced MRT studies with histological findings has shown that no enhancement area corresponded to necrotic lesions in paticnts with OsteonecroSis of the femoral head (5,27). On the other hand, Li and Hietle (10) reported that fat-suppression T1-weighted MRI enhanced with gadolinium-DTPA showed homogeneous or marginal enhancement in patients with osteonecrosis of the iemoral head, and Peiss et al (18) indicatcd that T1-weighted MRT enhanced with gadolinium-DTPA showed homogcneous enhancement in patients with osteonecrosis of the elbow. The differences in enhancement patterns may depend on the duration from onsct to the stage ofosteonecrosis of the temoral head.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, a comparison of some contrast-enhanced MRT studies with histological findings has shown that no enhancement area corresponded to necrotic lesions in paticnts with OsteonecroSis of the femoral head (5,27). On the other hand, Li and Hietle (10) reported that fat-suppression T1-weighted MRI enhanced with gadolinium-DTPA showed homogeneous or marginal enhancement in patients with osteonecrosis of the iemoral head, and Peiss et al (18) indicatcd that T1-weighted MRT enhanced with gadolinium-DTPA showed homogcneous enhancement in patients with osteonecrosis of the elbow. The differences in enhancement patterns may depend on the duration from onsct to the stage ofosteonecrosis of the temoral head.…”
Section: Discussionmentioning
confidence: 99%
“…There were two normal enhancement patterns on T1-weighted or fat-suppression T1 -weighted image5 cnhanccd with gadolinium-DTPA: no enhancement (three of 34 femora in group A and one of 25 in group B) and venous enhancement (three of 34 femora in group A and four of 25 in group B). There were also two abnormal enhancement patterns: focal homogeneous enhancement (22 of 34 temora in group A and 18 All femora wii ti lrohecular necroris (osteonecmsi?) had niarrow iicci-nsis.…”
Section: Mri Studymentioning
confidence: 99%
“…26,27,29,35 Furthermore, fragment enhancement implies presence of vascularity and viability. 7,18,36 Takamara and colleagues proposed a comprehensive classification system for OCD stability based on a combination of imaging and clinical features (►Table 4). In a 9-year review by Jars and colleagues, the prevalence and sensitivity of unstable osteochondral lesions in the elbow were reported.…”
Section: Computed Tomography and Computed Tomography Arthrographymentioning
confidence: 99%
“…MRI and CT are of no use in the evaluation of integrity of LUCL (OʼDriscoll et al 1991). MRI can be useful for detection of chondral damage to the capitellum secondary to the recurrent subluxation of the radial head (Peiss 1995).…”
Section: Imagingmentioning
confidence: 99%